Analysis of metabolic differences between Jiaosu fermented from dendrobium flowers and stems based on untargeted metabolomics - Lihong Jiang; Xingjiang Li; Shuo Wang; Du Pan; Xuefeng Wu; Fengxu Guo; Dongdong Mu; Fuhuai Jia; Min Zhang (Heliyon, 2024)
Dendrobium officinale is an important traditional Chinese medicinal herb containing bioactive polysaccharides and alkaloids. This study characterized metabolite differences between jiaosu (fermented plant product) from Dendrobium flowers versus stems using untargeted metabolomics. The jiaosu was fermented by mixed fermentation of Saccharomyces cerevisiae, Lactobacillus bulgaricus and Streptococcus thermophilus. Liquid chromatography-mass spectrometry analysis identified 476 differentially expressed metabolites between the two Jiaosu products. Key results showed downregulation of flavonoid metabolism in Dendrobium Stems Edible Plant Jiaosu (SEP) but increased flavonoid synthesis in Dendrobium Flowers Edible Plant Jiaosu (FEP), likely an antioxidant response. SEP displayed upregulation of lignin metabolites with potential antioxidant properties. The findings demonstrate significant metabolite profile differences between SEP and FEP, providing the basis for developing functional jiaosu products targeting specific health benefits.